PearlAI: Hyperpersonalization and Hyperlocalization as New AI Affordances in Basic Education - Akinfolarin Seun; Abisoye Ajayi; Ruth Adesola Elumilade; Mforchive Abdoulaye Bobga; Thomas Jerome Yeboah; Samuel Darkey Ofori; Adeniyi Adebowale Apelehin; Dennis Edache Abutu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Persistent challenges of engagement, equity, and learning outcomes continue to undermine basic education across Africa and other resource-constrained regions. Traditional curricula and teaching models are often generic, culturally distant, and unable to address the diverse learning needs of students in marginalized communities. This paper explores the transformative potential of hyperpersonalization and hyperlocalization, two emergent affordances enabled by artificial intelligence (AI), to reimagine education in these contexts. Hyperlocalization allows for curriculum and content to be rooted in community-specific languages, histories, and lived experiences, thereby overcoming cultural irrelevance and enhancing representation. Hyperpersonalization enables adaptive, student-centred learning pathways that respond to individual interests, paces, and strengths, reducing performance gaps and fostering deeper engagement. Together, these affordances extend beyond traditional differentiated instruction by embedding agency, belonging, and contextual relevance directly into the design of learning experiences. Drawing on global case studies, including personalized learning in India, national device rollouts in Uruguay and Kenya, and mobile literacy interventions in Africa, the paper situates PearlAI as a prototype framework capable of operationalizing these concepts. While not all educational challenges can be resolved through technology, evidence suggests that hyperpersonalization and hyperlocalization hold promise for addressing critical barriers such as cultural disengagement, inequity, and limited student agency. By integrating these affordances into the PearlAI ecosystem, this paper argues that AI can shift personalization and contextualization from a luxury into a basic educational utility—one that fosters equity, resilience, and relevance in the twenty-first-century classroom.